2007
DOI: 10.1243/13506501jet219
|View full text |Cite
|
Sign up to set email alerts
|

Elastohydrodynamic modelling of heat partition in rolling-sliding point contacts

Abstract: This article presents the results of a series of thermal elastohydrodynamic lubrication (EHL) analyses of a set of disc experiments carried out by Patching et al. The authors have previously calculated the heat partition at each load stage from the experimental data, and the present work seeks to compare the heat partition developed in a thermal EHL analysis of the lubricant film with that calculated from the experiments. These EHL analyses show that the heat partition depends on the non-Newtonian formulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Their result largely agreed with those found in this article that heat partition favoured the faster moving surface. To understand the origins of these phenomena, Evans et al compared their experimental heat partition with a thermal EHL analysis using a range of rheological models of lubricant behaviour [34]. It was found that heat partition results agreed only when wall-slip occurred at the faster moving surface (i.e.…”
Section: Temperature Mapsmentioning
confidence: 99%
“…Their result largely agreed with those found in this article that heat partition favoured the faster moving surface. To understand the origins of these phenomena, Evans et al compared their experimental heat partition with a thermal EHL analysis using a range of rheological models of lubricant behaviour [34]. It was found that heat partition results agreed only when wall-slip occurred at the faster moving surface (i.e.…”
Section: Temperature Mapsmentioning
confidence: 99%
“…The work presented by Merritt [9] indicates that if "the oil film offers no resistance to heat flow" and the flash contact temperatures of the disks are equal, then calculation of equal Block flash temperatures for the disks leads to Table 1 are higher than this as might be expected given that the mean surface temperature difference between the disks varies between 15 °C and 53 °C over the experiments, with the higher temperature in the faster disk. Numerical analyses of the EHL oil film using a variety of viscosity and non-Newtonian rheological models [12] have shown that the values of b obtained from thermal EHL considerations are generally less than 0.5 if the shear heating is dissipated in a distributed way across the oil film, and values of b greater than 0.6 are only obtained if the rheological model results in lubricant slip within the film at or near to the higher temperature surface. It is instructive to note that, for all of the combinations of viscosity and rheological models considered in [12], the calculated frictional traction matched that measured in experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating Q film and Q fr for the contacts used in the experiment using data for film temperature and thickness from [11] and [12] shows that Q fr exceeds Q film by a factor of between 500 and 1200, and consequently that Q film can be disregarded as being negligible.…”
Section: Thermal Model Of Test Diskmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption appears reasonable for small and moderate sliding velocities, which was the case in these experiments. Clarke et al [31] studied the high sliding velocity case and concluded that shearing occurs near the faster surface, with effects on temperature distribution and heat transfer of the contact surfaces.…”
Section: Traction Modelmentioning
confidence: 99%